2021
DOI: 10.1002/anie.202108847
|View full text |Cite
|
Sign up to set email alerts
|

Diarylethene‐Based Photoswitchable Inhibitors of Serine Proteases

Abstract: A bicyclic peptide scaffold was chemically adapted to generate diarylethene‐based photoswitchable inhibitors of serine protease Bos taurus trypsin 1 (T1). Starting from a prototype molecule—sunflower trypsin inhibitor‐1 (SFTI‐1)—we obtained light‐controllable inhibitors of T1 with Ki in the low nanomolar range, whose activity could be modulated over 20‐fold by irradiation. The inhibitory potency as well as resistance to proteolytic degradation were systematically studied on a series of 17 SFTI‐1 analogues. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 70 publications
(52 reference statements)
0
20
0
Order By: Relevance
“…The photochromic DTE moiety has also been utilised as a means to achieve photoswitchable inhibition of serine proteases (Figure 9). [50] Known bicyclic peptidic inhibitor, SFTI‐1, of the serine protease Bos taurus typsin 1 (T1) consists of two loops stabilised by a disulfide bridge, whereby the reactive loop binds the serine protease. The DTE‐derived peptidic inhibitor 46 was realised by merging the photoswitching unit into the structural loop of SFTI‐1, which does not interact with the active site of the enzyme.…”
Section: Light‐responsive Protease Inhibitorsmentioning
confidence: 99%
“…The photochromic DTE moiety has also been utilised as a means to achieve photoswitchable inhibition of serine proteases (Figure 9). [50] Known bicyclic peptidic inhibitor, SFTI‐1, of the serine protease Bos taurus typsin 1 (T1) consists of two loops stabilised by a disulfide bridge, whereby the reactive loop binds the serine protease. The DTE‐derived peptidic inhibitor 46 was realised by merging the photoswitching unit into the structural loop of SFTI‐1, which does not interact with the active site of the enzyme.…”
Section: Light‐responsive Protease Inhibitorsmentioning
confidence: 99%
“…[17][18][19][20] For example, it has been reported that diarylethene and its derivates can undergo efficient and reversible photochromism when irradiated with UV and visible light, ultimately allowing control of the luminescence of such compounds. [21][22][23][24][25] The combination of NIR phosphorescence and photochromism in a single diarylethene molecule could therefore render such a system widely applicable in various fields. However, to the best of our knowledge, photo-controlled pure organic NIR phosphorescence has yet to be reported in solution.…”
Section: Doi: 101002/smll202201821mentioning
confidence: 99%
“…[13][14][15] These strategies have been successfully applied to diverse targets, including enzymes [1,3,7] and transmembrane proteins, [6,12] as well as peptides or proteins that modulate the activity of these targets, such as enzyme inhibitors. [16][17][18] For the latter, tuneable activity is particularly useful as it can shift the inhibitor's influence on its intended target or pathway. [16][17][18] However, efforts to engineer peptide-based inhibitors with switchable activity have been largely confined to relatively short peptides with non-complex topologies.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] For the latter, tuneable activity is particularly useful as it can shift the inhibitor's influence on its intended target or pathway. [16][17][18] However, efforts to engineer peptide-based inhibitors with switchable activity have been largely confined to relatively short peptides with non-complex topologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation